URGENSI KAFAAH DALAM PERNIKAHAN MENURUT MASYARAKAT DESA BUMIAJI KECAMATAN BUMIAJI KOTA BATU - Qurrota A’yunnisa; Ibnu Jazari; Moh. Muslim (Jurnal Hikmatina, 2022)
Married couples must be able to actualize them in building household harmony, so that the goals of a successful marriage, mawaddah, wahrahah can be achieved. In order to form and create a family of faith, mawaddah, wa rahmah, scholars recommend that there be balance, unity, equality (there is an element of kafa'ah) between the prospective husband and wife. Each man has his own way and purpose, so the Messenger of Allah limits him in four factors: wealth, children, beauty, and religion. In this study, researchers used unstructured or free interview techniques with the aim of finding more in-depth information about the urgency of kafa'ah according to the people of Bumiaji Village, Bumiaji District, Batu City. Kafa'ah in marriage to the people of Bumiaji Village Batu urgency showed an interest in something in determining an action. In this case, the urgency of the kafa'ah in Bumiaji Village has only been achieved in terms of its people's wealth, education, and work alone, in terms of religion, it still cannot be fully achieved or only a small part has already been effected'. If there is a lack of trust that leads to divorce, the Bumiaji village government can only help with mediation and the rest are administratively handed back to each spouse and family.Keyword: kafa’ah, marriage